2006
DOI: 10.1159/000094536
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Promoter Polymorphisms within the NOS3 Gene and Allergic Diseases

Abstract: Background: Nitric oxide (NO) is an important mediator of physiologic and pathologic processes in the airways. On this basis, we hypothesized that polymorphisms in the NOS3 gene could be associated with the disease process. Methods: Two promoter variants (–786C/T and –691C/T) were examined in a Caucasian Czech population of allergic patients [n = 671, with a subgroup of asthmatics (n = 305)] and healthy controls (n = 334) using PCR-RFLP analyses. Results: NOS3 –786C/T and –691C/T were not associated with aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…However, the protective effect against asthma associated with the common -786T/-691C/27-bp 5 repeat variant/ 774C/894G/11T haplotype that we reported in the present study confirms our previous findings obtained only with the analysis of individual polymorphisms, in which we determined a relationship between the polymorphism in intron 4 of the eNOS gene and the intermediary atopic phenotypes [21] and between the promoter variant -786C/T and asthma in males [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the protective effect against asthma associated with the common -786T/-691C/27-bp 5 repeat variant/ 774C/894G/11T haplotype that we reported in the present study confirms our previous findings obtained only with the analysis of individual polymorphisms, in which we determined a relationship between the polymorphism in intron 4 of the eNOS gene and the intermediary atopic phenotypes [21] and between the promoter variant -786C/T and asthma in males [25].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it is possible that our haplotypes interact with other NO-producing (NOS1 and NOS2) or asthma candidate genes or possibly with other factors such as hormonal balance. In a recent study we observed a significant interaction between eNOS-786C/T variant and gender [25]. Previously, our group studied polymorphic markers in nNOS (C5266T) and iNOS (several variants mainly in promoter region) genes and reported significant associations between the nNOS variant and plasma IgE [41], similar to that between iNOS haplotypes and asthma [42].…”
Section: Discussionmentioning
confidence: 63%
“…However, the present sample is exclusively of Czech Caucasian origin, restricted to the limited geographical area populated by a quite homogenous population with little admixture. Third, there are certainly other genes and polymorphisms – e.g., of superoxide dismutase, nitric oxide synthase, catalase – that could modulate antioxidant properties and thus are a predisposition to asthma [30,31,32,33,34], which have not been studied in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Six were selected based on the literature (ie, previously reported association with FENO, asthma, and other respiratory phenotypes) rs2682826,20 rs41279104,28 rs2255929,29 rs3918226,30 rs3918169,30 rs154975831 and were complemented with 48 tagging SNPs to capture genetic variation across each gene (supplementary table 1). Tag SNP selection was done using the HapMap phase III European ancestry data (http://www.hapmap.org) with a pairwise approach (r 2 ≥0.8) for SNPs with minor allele frequency ≥0.05, extending to 100 kb upstream and 50 kb downstream of each gene.…”
Section: Methodsmentioning
confidence: 99%